Relationships between parental involvement, health knowledge, attitudes, and practices and biopsychosocial well-being of children in metropolitan cities, Peninsular Malaysia - Chua, Yee Weun (2017)
The main purpose of this study was to determine the relationships between parental involvement, children’s health knowledge, attitudes, and practices (KAP) and children’s biopsychosocial well-being. In addition, the study assessed the mediating effect of health KAP on the relationships between parental involvement and biopsychosocial well-being among children. A total of 450 students aged between 10 and 12 years old from 15 schools in metropolitan cities in Peninsular Malaysia were selected as respondents using Probability Proportionate-to-Size (PPS) sampling technique. Self-administered questionnaire with standardized instruments was used for data collection. Parental involvement was measured with Perception of Parents Scale (POPS) (Grolnick et al., 1991); health knowledge, attitudes, and practices was measured with Nutrition Knowledge Questionnaire (Volpe & Huang, 2004), Activity Knowledge Scale (AKQ) (Melnyk & Small, 2003a), Healthy Living Attitudes Scale (Melnyk & Small, 2003b) and Healthy Lifestyle Behaviour Scale (Melnyk & Small, 2003c) respectively; while biopsychosocial well-being was measured with The PedsQL 4.0 (Pediatric Quality of Life Inventory) Genetic Core Scales (Varni et al., 2001). Results from the hierarchical regression analysis showed that older children who experienced greater maternal and paternal involvement tend to report greater overall biopsychosocial well-being. Further analyses indicated that children’s health knowledge, attitudes, and practices have both partial and full mediating effect on the relationship between parental involvement and biopsychosocial well-being. Specifically, the inclusion of activity knowledge, nutrition knowledge and healthy living attitudes in the mediation model resulted in the decreased of direct influence of maternal involvement on biopsychosocial well-being among children. Findings from the study implied that parental involvement promote better biopsychosocial well-being among children. Besides that, the test of the mediating models showed the significant mediating effect of children’s activity knowledge and healthy living attitudes in the relationships between parental involvement and overall and specific biopsychosocial well-being, specifically in the domain of social functioning. Thus, it can be concluded that positive involvement from parents may improve their children’s health knowledge and promote healthy living attitudes, which eventually contribute to better biopsychosocial well-being. Findings from the current study may have practical implications for individuals, parents, schools, practitioners and governmental agencies who are directly involved in children welfare and programs development. In specific, programmes that focus directly on developing and improving children’s health knowledge, attitudes, and practices, together with the involvement of supportive parents, will enhance children’s biopsychosocial well-being and may eventually lead to successful transition to adulthood.